Pengaruh Profitabilitas dan Aktivitas terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi pada Perusahaan Property dan Real Estate - Trixie Ridasiena Ariosafira; Rahman Amrullah Suwaidi (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study is to analyze the influence of the relationship between profitability and activity on company value and capital structure used as a moderation variable in property and real estate sector companies listed on the IDX for the period 2018 to 2020. The study's population included 79 companies. Purposive sampling in this study was used as a sampling method and obtained by as many as 47 companies. Moderated Regression Analysis is an analytical technique used in this test. The results of this study show that the variables of profitability and activity contribute significantly positively to the value of the company, while the variable of capital structure as a moderation variable is not able to strengthen the relationship between profitability and activity with the value of the company.